Compact and Circular Polarized RFID Antenna for Portable Terminal Applications - Yuan Yao; Youbo Zhang; Junsheng Yu; Xiaodong Chen (International Journal of Antennas and Propagation)
A novel compact and circular polarized antenna is proposed which can be easily fabricated and embedded into RFID readers. Circular polarization characteristic of the proposed antenna is achieved by introducing a crossed branch. The modified meandering line structure gives the antenna compactness characteristic. A prototype is fabricated and measured. The results show that this circular polarized antenna with compact dimension can cover the Chinese RFID operating band from 920 MHz to 925 MHz, which make's the antenna suitable for handheld terminal application of RFID readers.